“The Maasai Need Cows and the Cows Need Maasai,” the Use of a Photovoice Approach to Assess Animal Health Needs - van der Meer, Frank; Clancy, Eoin; Thomas, Adam; Kutz, Susan; Hatfield, Jennifer; Orsel, Karin (Frontiers in Veterinary Science, 2015)
The Maasai pastoralists in sub-Saharan Africa depend on their livestock for income and food. Livestock production can be significantly improved by addressing animal health concerns. We explored the use of photovoice, a participatory action research method, to strengthen our understanding of the Maasai’s animal health needs. Nine interviewees, representing warriors, elders, and women, identified animal, social, and human health themes. The use of photography provided a new medium for Maasai to express their needs and a focus for researcher-participant communications, thereby facilitating new insights across language and cultural barriers.